ISLAMIC DIGITAL MARKETING ASSISTANCE MODEL OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN BANDA ACEH CITY, INDONESIA - Jasafat Jasafat; Rusnawati Rusnawati; Syahril Furqany; Sabirin Sabirin (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2021)
The integrated mentoring model with a practical and applicable approach has been widely applied to various institutions, both formal and non-formal. However, this model has not been applied in the development of Micro, Small, and Medium Enterprises (MSMEs). This situation is due to the assumption that MSMEs are independent businesses, not related to the government or other institutions. Data from the Department of Industry and Trade of Cooperatives and MSMEs shows that in Banda Aceh until now the government does not yet have a model of assistance in promotion and marketing with a communication technology approach, especially in the use of social media. This article aims to provide a response to the condition of MSMEs that have not received special assistance in the use of communication technology (websites and social media) in marketing and the benefits obtained by MSMEs before and after receiving assistance. This article uses qualitative data using Participatory Action Research (PAR) techniques through observation, interviews, and participants. This study found that MSMEs in Banda Aceh need communication technology (websites and social media) as a means of promotion and marketing, the mentoring program requires a new model of marketing and promotion. This article provides knowledge to MSMEs on the importance of using social media as a means of promotion. In addition, the impact of digital marketing is very real, not only for profit but for Muslim entrepreneurs it can be used as a means of preaching. Such as inserting calls to pray, fast, pay zakat, and other messages that invite goodness and prevent evil (Amar Ma'ruf Nahi Munkar).